2015
DOI: 10.1038/onc.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cytokinesis: the emerging roles of CEP55 in tumorigenesis

Abstract: CEP55 was initially identified as a pivotal component of abscission, the final stage of cytokinesis, serving to regulate the physical separation of two daughter cells. Over the past 10 years, several studies have illuminated additional roles for CEP55 including regulating the PI3K/AKT pathway and midbody fate. Concurrently, CEP55 has been studied in the context of cancers including those of the breast, lung, colon and liver. CEP55 overexpression has been found to significantly correlate with tumor stage, aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
122
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 85 publications
11
122
0
Order By: Relevance
“…Through the combined application of homozygosity mapping and exome sequencing, we identified the likely causative genetic defect, a nonsense mutation in CEP55 (c.1274C>A; p.S425X), which encodes centrosomal protein-55 kDa (CEP55). Although not implicated previously in any genetic disorder, CEP55 is known to be essential for the final step of cytokinesis, abscission and has also been found to be upregulated in some tumours 5. More recently, loss of cep55l, the zebrafish ortholog of CEP55 , was also shown to result in various developmental defects in zebrafish embryos 6.…”
Section: Introductionmentioning
confidence: 99%
“…Through the combined application of homozygosity mapping and exome sequencing, we identified the likely causative genetic defect, a nonsense mutation in CEP55 (c.1274C>A; p.S425X), which encodes centrosomal protein-55 kDa (CEP55). Although not implicated previously in any genetic disorder, CEP55 is known to be essential for the final step of cytokinesis, abscission and has also been found to be upregulated in some tumours 5. More recently, loss of cep55l, the zebrafish ortholog of CEP55 , was also shown to result in various developmental defects in zebrafish embryos 6.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences have shown CEP55 is highly expressed in several cancers including human colon cancer and lung cancer (7)(8)(9)(10). Interestingly, CEP55 has been demonstrated to be involved in tumorigenesis of breast cancer (11)(12)(13). However, the functional role of CEP55 in breast cancer is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, overexpression of CEP55 was found in lung adenocarcinoma, gastric carcinoma and hepatocellular carcinoma, where it promote cell proliferation and invasion (17,21,22). It was among the top 70 most highly overexpressed genes in an analysis across 12 cancer types including lung, lymphoma, medulloblastoma and breast, and was identified in prognostic signatures for these cancers (18,23). In this study, we found that CEP55 expression increased significantly in glioma and GBM U251 cells than in normal brain tissue.…”
Section: Discussionmentioning
confidence: 58%
“…CEP55 is a conserved gene to preventing genetic damage and its protein acts as a regulator of cell cycle progression ensuring proper abscission, the final stage of cytokinesis (18). Therefore, the expression of CEP55 might be regulated by other driver gene.…”
Section: Egfrviii Promoted the Proliferation And Expression Of Cep55 mentioning
confidence: 99%